2013
DOI: 10.1177/193229681300700504
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Thermal Imaging for Automated Detection of Diabetic Foot Complications

Abstract: Abbreviations: (ROI) region of interest, (SD) standard deviationKeywords: automatic detection, diabetic foot, infrared imaging, prevention, telemedicine, thermography

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
100
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(111 citation statements)
references
References 20 publications
0
100
0
11
Order By: Relevance
“…Several studies have used thermography in diagnostic cases of neoplasias [18], muscle damage [19, 20], ischemia in diabetes [21], and evaluation and recovery of muscle function [17]. However, few studies have used this tool in the field of neurology and future research is suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used thermography in diagnostic cases of neoplasias [18], muscle damage [19, 20], ischemia in diabetes [21], and evaluation and recovery of muscle function [17]. However, few studies have used this tool in the field of neurology and future research is suggested.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular infiltrations with an extensive vascular component (vasodilatation, edema exudation) are responsible for an increase in the heat generation at the injection site that can be measured by an IR camera [10]. Changes from 0.2 to 2 • C have been demonstrated in inflammatory dermatologic processes [20,[24][25][26].…”
Section: Discussionmentioning
confidence: 98%
“…There have been several encouraging reports of infrared imaging being used as a non-invasive diagnostic tool for perfusion abnormalities 3, 4. Nevertheless, thermography methods have not yet become widely established in clinical medicine.…”
Section: Discussionmentioning
confidence: 99%